Computational Logic in Multi-Agent Systems 15th International Workshop, CLIMA XV, Prague, Czech Republic, August 18-19, 2014, Proceedings - Bulling, Nils.; van der Torre, Leendert; Villata, Serena; Jamroga, Wojtek; Vasconcelos, Wamberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the proceedings of the 15th International Workshop on Computational Logic in Multi-Agent Systems, CLIMA XV, held in Prague, Czech Republic, in August 2014. The 12 regular papers were carefully reviewed and selected from 20 submissions. The purpose of the CLIMA workshops is to provide a forum for discussing techniques, based on computational logic, for representing, programming and reasoning about agents and multi-agent systems in a formal way. This edition will feature two special sessions: logics for agreement technologies and logics for games, strategic reasoning, and social choice.
Keywords: Artificial intelligence; Machine theory; Software engineering; Compilers (Computer programs).; Computer science; Application software; Artificial Intelligence; Formal Languages and Automata Theory; Software Engineering; Compilers and Interpreters; Computer Science Logic and Foundations of Programming; Computer and Information Systems Applications